2003
DOI: 10.6090/jarq.37.99
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Specific Low-Molecular-Weight-Glutenin Subunits Related to Gluten Quality in Bread Wheats

Abstract: We studied single seed descent lines derived from the Kitakeiharu 717 (KKS 717) / Grandin cross. The presence of a B subunit of KKS 717-specific low-molecular-weight-glutenin subunit (LMW-GS) significantly enhanced the gluten strength. Although the C subunit showing a difference in mobility between Grandin and KKS 717 did not affect the gluten strength, the presence of this KKS 717-specific C subunit significantly decreased the gluten index in the absence of the KKS 717-specific B subunit. Using a LMW-GS locus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 13 publications
0
7
0
4
Order By: Relevance
“…Low molecular weight (LMW) glutenins are encoded by genes on the short arm of chromosome 1 and are closely linked to gliadin loci. Recent reports demonstrate that alternative alleles of the LMW glutenin-gliadin loci can alter breadmaking traits, especially dough strength (Nieto-Taladriz et al 1993;Manifesto et al 1998;Branlard et al 2001;Ikeda et al 2003).…”
mentioning
confidence: 99%
“…Low molecular weight (LMW) glutenins are encoded by genes on the short arm of chromosome 1 and are closely linked to gliadin loci. Recent reports demonstrate that alternative alleles of the LMW glutenin-gliadin loci can alter breadmaking traits, especially dough strength (Nieto-Taladriz et al 1993;Manifesto et al 1998;Branlard et al 2001;Ikeda et al 2003).…”
mentioning
confidence: 99%
“…Takata et al (2000) reported the effect of HMW-GSs on the bread-making quality under Harunoakebono background. Ikeda et al (2003) reported that a LMW-GS encoded by the Glu-A3 in Kitakeiharu 717 enhanced the gluten strength. Maruyama-Funatsuki et al (2005) reported that HMW-GS 5 + 10 with LMW-GS 42 kDa showed interactive effects on the bread-making quality and led to the increase of the dough strength that became comparable to that of Canada Western Extra-Strong wheat.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently, emphasis had been placed on breeding cultivars suitable for the production of Japanese white salty noodles, though a few cultivars had been bred for breadmaking quality and contained 5 + 10 subunits (Nakamura et al 1999). A few studies on the effect of the Glu-1 and Glu-3 alleles, and their interaction, on the gluten properties have been conducted using Japanese cultivars (Ikeda et al 2003, Maruyama-Funatsuki et al 2005, Nagamine et al 2000, Takata et al 2000. Takata et al (2000) reported the effect of HMW-GSs on the bread-making quality under Harunoakebono background.…”
Section: Introductionmentioning
confidence: 99%
“…Alternative alleles at the glutenin and gliadin loci can alter bread-making traits, especially dough strength (Branlard, Dardevet, Saccomano, Lagoutte, & Gourdon, 2001;Ikeda, Nakamichi, Nagamine, Yano, & Yanagisawa, 2003;Manifesto, Feingold, Hopp, Schlatter, & Dubcovsky, 1998;Nieto-Taladriz, Perretant, & Rousset, 1993). The wheat kernel contains two classes of gluten storage proteins, including monomeric gliadin proteins and polymeric glutenin proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Low molecular weight glutenins are encoded by genes on the short arm of chromosome 1 and are closely linked to gliadin loci. Alternative alleles at the glutenin and gliadin loci can alter bread-making traits, especially dough strength (Branlard, Dardevet, Saccomano, Lagoutte, & Gourdon, 2001;Ikeda, Nakamichi, Nagamine, Yano, & Yanagisawa, 2003;Manifesto, Feingold, Hopp, Schlatter, & Dubcovsky, 1998;Nieto-Taladriz, Perretant, & Rousset, 1993).…”
Section: Introductionmentioning
confidence: 99%